Pore Network Modeling of Core Forming Melts in Planetesimals - Solferino, Giulio F. D.; Thomson, Paul-Ross; Hier-Majumder, Saswata (Frontiers in Earth Science, 2020)
Early in the history of the solar system, planetesimals were differentiated into metallic cores. In some planetesimals, this differentiation took place by percolation of the denser core forming liquid through a lighter solid silicate matrix. A key factor in core formation by percolation is the establishment of a connection threshold of the melt. In this work, we report new results from pore network modeling of 3D microtomographic images of 11 synthetic olivine aggregates containing Fe-FeS melt. Our results demonstrate that a melt volume fraction of 0.14 is required to achieve connectivity of the melt. We also show that surface-tension driven melt segregation during annealing experiments plays an important role in controlling this threshold melt fraction. We also report that, contrary to the generally accepted notion, melt pinch-off is caused by reduction in pore size, rather than melt drainage out of throats. Using the results of our study, we estimate that the peak melt segregation velocity in a planetesimal of 100 km radius can be as high as 41 m/yr and core segregation can be completed in less than 0.5 million years.